Prevalence and predictors of misperceptions of 'better-for-you' alcohol products among Australian adult drinkers. - Haynes, Ashleigh; Ilchenko, Elizaveta; Dixon, Helen; Morley, Belinda (Health Promotion International, 2024)
This study investigated the prevalence and predictors of misperceptions about the healthiness of alcohol products carrying common health-oriented marketing cues and the relative importance of the type (versus amount) of alcohol consumed in contributing to health risks. Data were from a 2022 cross-sectional national population survey. Australian adults (18–65 years) who consumed alcohol in the past year (n  = 1960) reported their agreement with statements that a selection of health-oriented marketing cues meant an alcohol product was 'better for you' and rated the importance of the type and amount of alcohol consumed in causing health risks. The majority of participants misperceived the type of alcohol to be at least as important as the amount in causing health risks (61%) and misperceived at least one health-oriented marketing cue as meaning a product was 'better for you' (75%). Misperceptions about low sugar, calorie and carbohydrate; and preservative-free claims (46–56%) were most common. Misperceptions about natural, organic, vegan, low sugar, low calorie, gluten-free and seltzer cues were less prevalent among older (45–65 years) than young adults (18–24 years, PR = 0.27–0.86). A lower proportion of women (compared to men) held misperceptions about vegan (PR = 0.66) and gluten-free claims (PR = 0.78), but a higher proportion held misperceptions about low sugar claims (PR = 1.13). There were also variations by socioeconomic status, alcohol consumption, education and regional/metropolitan location. Misperceptions about health-oriented marketing of alcohol are widespread. Further regulation of permissible alcohol marketing content is needed, but until then, differences in misperceptions between population segments may inform targeted health promotion efforts.